The Impact of Brand Image on Consumer Behaviour of Luxury Goods of Fashion Industry in China - Cheng, Chi-Wen (2006)
When we are marching into the next century, we have been witnessing China emerge as a great economic entity in the world. China, as a newly emerging market, has many affluent opportunities to be discovered and developed by business organisations from different industries. With the great population and the government's liberalising attitude, China has made itself an auspicious country for luxury goods of fashion industry. Consequently, it is significant for marketers to understand how Chinese consumers' behave and what their attitude is so as to tap the astronomical opportunity in China.